Persepsi Mahasiswa Universitas Tadulako Dalam Pidato Kampanye Ahmad Ali Pada Pilkada Sulteng 2024 - Junaedi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This research aims to understand the perceptions of FISIP students at Tadulako University regarding Ahmad Ali's campaign speech in the 2024 Sulteng regional elections The method used in this study is qualitative descriptive research. The data collection techniques employed are observation, interviews, and documentation. The subjects of the research are FISIP students at Tadulako University majoring in communication studies, government science, and sociology who witnessed Ahmad Ali's campaign speech either directly or through social media platforms such as Instagram and TikTok.The results provide valuable insights into how FISIP students at Tadulako University perceive the campaign speech. This research indicates the need for a deeper understanding of the audience, as well as the application of effective communication techniques to achieve success in political campaigns.